Fleksibilitas Transparansi dan Akuntabilitas dalam Menghindari Penipuan dengan Pendekatan Akuntansi Forensik: Blawi Lamongan - Wijaya, Almaira Oktavia; Leniwati, Driana; Wahyuni, Endang Dwi; Astuti, Sri Wibawani Wahyuning; Affan, Muhammad Wildan (Universitas Jember, 2024)
This research aims to find out how a village can flexibly account for its village funds in a transparent manner to minimize acts of fraud by using a forensic accounting approach considering the increasing number of cases related to these acts. Data collection was carried out through in-depth interviews with village officials who were key informants. The method used was snowballing with additional informants. The resulting interview will then be concluded or summarized. Then a triangulation technique was carried out by conducting interviews and checking validity by viewing or observing existing websites so that the data obtained was valid. Based on the results found in the research, it can be concluded that accountability of village funds is needed to minimize this situation, but there are still several factors that make this an opportunity, such as a person's lack of trust in existing temptations and the demands of the people around him who ask him to produce more money. Keywords: Accountability, Forensic Accounting, Flexibility, Fraud